2011
DOI: 10.1177/0309364610394476
|View full text |Cite
|
Sign up to set email alerts
|

Central fabrication

Abstract: In this research we investigated the degree of error during the carving phase of central fabrication of prosthetic sockets for people with limb amputation. Three different model shapes were ordered from each of ten central fabrication companies. Using an accurate custom mechanical digitizer and alignment algorithm, we digitized the models and then compared the model shapes with the electronic file shapes. Results showed that 24 of the 30 models had volumes larger than the electronic file shapes while 24 had vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In postprocessing algorithms, we corrected for vertical translation of the stylus tip from rotation of the stylus arm about the RVDT axis. The instrument had a radial resolution better than 0.08 mm and measured socket volume differences less than 0.1 percent [12]. We measured each socket from the patellar tendon to the distal end at cross-sections spaced at 0.8 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In postprocessing algorithms, we corrected for vertical translation of the stylus tip from rotation of the stylus arm about the RVDT axis. The instrument had a radial resolution better than 0.08 mm and measured socket volume differences less than 0.1 percent [12]. We measured each socket from the patellar tendon to the distal end at cross-sections spaced at 0.8 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, we found considerable variability in the quality of prosthetic sockets fabricated by central fabrication facilities using computer-socket manufacturing methods [12]. Fabrication errors might not be identified by the practitioner until the socket is test-fit to the patient because errors are often hard to see by eye.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly shown in previous reports in the literature [2,10], variability exists in quality and consistency among different fabrication facilities that make prosthetic models and sockets for patients with amputation. It would therefore seem reasonable for facilities to assess their manufacturing equipment as part of their regular practice.…”
Section: Discussionmentioning
confidence: 96%
“…The RadialWeight was 0.2 and the NormalWeight was 0.8. The basis for selecting these weights was prior clinical experience where we found that a RadialWeight/NormalWeight of 0.8/0.2 performed well for comparing residual limb shapes and 0.2/0.8 worked well for comparing socket shapes [7,8,9]. …”
Section: Methodsmentioning
confidence: 99%
“…Locations in which they do align well are white. These metrics were selected because similar metrics were used effectively in previous research assessing manufacturing quality of prosthetic sockets [6] and positive models [9], and the clinical impact of socket shape error [8]. Radial difference data has been used effectively in commercial software packages in the prosthetics industry for socket design to compare socket and limb shapes.…”
Section: Methodsmentioning
confidence: 99%